Umm Kulthum: Artistic Agency and the Shaping of an Arab Legend, 1967-2007. Laura Lohman. 2010. Middle Town, CT: Wesleyan University Press. 229 pp. - Amoros, Luis Gimenez (International Library of African Music, 2012)
pages: 186-188
Keywords: African Music